QUALIDADE DE VIDA, SUPORTE SOCIAL E CONTROLE GLICÊMICO EM PORTADORES DE DIABETES MELLITUS TIPO2 - Franco Júnior, Alberto José de Amorim (2010)
Diabetes Mellitus is a chronic degenerative disease that requires a lot of limitations due to the need for constant treatment. Therefore, it was considered that the study of life quality and social support could bring knowledge to improve the quality of interventions for these patients. The aim of this study was to evaluate the quality of life, social support and glycemic control in type2 diabetic patients. This is a descriptive and transversal study was conducted among 120 patients of both genders, who attended the outpatient endocrinology clinic of a hospital located in Sao Bernardo do Campo city. For data collection we used the following instruments: a questionnaire for population characteristics, quality of life questionnaire (WHOQOL-BREF) and the Scale of Perceived Social Support (EPSS). The data relating to glycemic control were collected from medical records of patients. For data analysis we used descriptive statistics and statistical tests (Pearson, Chi-square, Fisher exact, ANOVA and Post hoc). The results indicated that the field of social relations was the largest contributor to quality of life. And the variable time of diagnosis, insulin therapy, and number of dependents, education, diet and medication interfered with quality of life and quality of treatment. These results call attention to the medical evaluations should be tied to assessments of quality of life, social support and also variables that affect the quality of treatment for that in this way can resize or enhance doings related interventions with these patients.